Prenatal exposure to phenols and benzophenones in relation to markers of male reproductive function in adulthood - Holmboe, Stine A.; Scheutz Henriksen, Louise; Frederiksen, Hanne; Andersson, Anna-Maria; Priskorn, Lærke; Jørgensen, Niels; Juul, Anders; Toppari, Jorma; Skakkebæk, Niels E.; Main, Katharina M. (Frontiers in Endocrinology, 2022)
Environmental exposure during fetal life may disrupt testicular development. In humans, a limited number of studies have investigated whether these adverse effects persist into adulthood. Using data from a prospective, population-based birth cohort study, The Copenhagen Mother-Child cohort, the objective was to assess if there is an association between fetal exposure to selected phenols and benzophenones and markers of testicular function in adult men. Pregnant women were recruited in 1997–2001. Their sons were examined clinically at 18-20 years of age, with focus on adult markers of reproductive function (anogenital distance (AGD), semen quality and reproductive hormones). In total, 101 18–20-year-old men were included, whose mothers during pregnancy had a serum sample drawn and analyzed for bisphenol A (BPA) and seven other simple phenols, as well as six benzophenones. To investigate the association between chemical levels (in tertiles, T1-T3) in relation to markers of reproductive function, univariate and multiple linear regression analyses were performed. In fully adjusted analyses, increased levels of luteinizing hormone (LH) were observed with higher fetal exposure to BPA (β (95%CI)) (T2: 12% (-8%,36%) and T3: 33% (10%,62%), compared to T1) and benzophenone-3 (BP-3) (T2: 21% (-2%,49%), T3: 18% (-4%,45%)), while no clear association was seen to total testosterone (TT). Higher levels of BPA and BP-3 were associated with a lower TT/LH ratio, although only significant for BPA (p-trend=0.01). No associations were seen to AGD or markers of semen quality. In conclusion, high exposure to BPA and BP-3 was associated with a compensated reduced Leydig cell function but no other changes in markers of reproductive health. As maternal levels of BPA and BP-3 were not correlated, separate effects may be at play. Larger studies on long-term reproductive consequences of prenatal exposures are warranted to validate our findings.